The Evolution of Humor Based on Local Wisdom: Social Message Marketing Strategies in the Social Media Era - Yusuf Effendi; Daniari Setiawati; Deddy Muharman (Yayasan Ilomata, 2026)
This study analyzes the framing of humor based on local wisdom as a social message delivery strategy on the YouTube platform, with a specific focus on the 'Log In Season 3' playlist. Using the qualitative content analysis method of video units and audience responses in the comment column, this study dissects the persuasion mechanism in digital narratives. The findings suggest that framing local humor plays a strategic role in normalizing criticism of sensitive issues such as gender stigma, religious tolerance, and mental health. Humor serves as a de-escalation mechanism that lowers audience resistance through peripheral pathways in the Elaboration Likelihood Model (ELM), where the communicator's attractiveness and credibility are the main cues for